1992
DOI: 10.1021/bi00116a021
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fatty acid oxygen-18 exchange catalyzed by pancreatic carboxylester lipase. 1. Mechanism and kinetic properties

Abstract: The exchange of 18O between H2O and long-chain free fatty acids is catalyzed by pancreatic carboxylester lipase (EC 1.1.1.13). For palmitic, oleic, and arachidonic acid in aqueous suspension and for 13,16-cis,cis-docosadienoic acid (DA) in monomolecular films, carboxyl oxygens were completely exchanged with water oxygens of the bulk aqueous phase. With enzyme at either substrate or catalytic concentrations in the argon-buffer interface, the exchange of DA oxygens obeyed a random sequential mechanism, i.e., 18O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
1
18
1
Order By: Relevance
“…When the enzyme was incubated with fatty acid and ethanol, an acyl-enzyme intermediate was formed and fatty acid ethyl ester was synthesized though nucleophilic displacement by ethanol. Exchange of fatty acid carboxyl oxygens with water oxygens was demonstrated by Muderhwa et al (18) using 18 O water. They suggested that fatty acids are good "substrates" for lipase(s).…”
Section: Discussionmentioning
confidence: 95%
“…When the enzyme was incubated with fatty acid and ethanol, an acyl-enzyme intermediate was formed and fatty acid ethyl ester was synthesized though nucleophilic displacement by ethanol. Exchange of fatty acid carboxyl oxygens with water oxygens was demonstrated by Muderhwa et al (18) using 18 O water. They suggested that fatty acids are good "substrates" for lipase(s).…”
Section: Discussionmentioning
confidence: 95%
“…31, No. 1, 1992 Muderhwa and Brockman oxygens of 13,16-cis,cis-docosadienoic acid (DA) in monolayers, the accessibility of the fatty acid by the enzyme can be monitored (Muderhwa et al, 1992). With monolayers of pure DA and a CEL concentration of 30 nM, exchange is essentially complete in 10 min.…”
Section: Resultsmentioning
confidence: 99%
“…Most reagents and procedures for CEL adsorption and l 8 0 exchange experiments were as described in the preceding paper (Muderhwa et al, 1992). All experiments were performed at pH 6.6 on a subphase containing 0.01 M potassium phosphate buffer and 0.1 M NaCl at 24 OC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al (1988) used the kinetic equations for sequential reactions to investigate the effect of taurocholate on human milk bile-salt-activated lipase. Muderhwa et al (1992) studied the exchange of "0 between water and fatty acids catalyzed by carboxylester lipase. We therefore believe that kinetic equations for sequential reactions are useful tools in studying lipolytic reactions.…”
Section: Discussionmentioning
confidence: 99%